Recensão de Decolonising English Studies From The Semiperiphery De Ana Cristina Mendes (2023) - Silva, Cristina Pinto da (E- Revista de Estudos Interculturais, 2023)
Some of us rather complacently thought that the old days of learning English through the adventures of a blond John, with an obedient Mary in tow, having tea and scones after visiting the Tower of London, were long gone. Academia, to be fair, was never this simplistic, and efforts to go beyond the canon have yielded a peppering of diversity in most curricula. More enlightened times, or so we thought. [...]